Students' Perception of Utilizing Podcasts to Learn English Listening Skill - Hersagita Anissa; Maman Suryaman (Universitas Sulawesi Barat, 2021)
In this day of advanced technology, learning English can be done anywhere, not just through books, but also through the internet. Podcasts can assist in learning listening English during this pandemic since they can be listened to anywhere and at any time, and podcasts are also an enjoyable media. The purpose of this study is to find out what students think about using podcasts to learn English. The research sample was made up of ten people between the ages of 18 until 21, who filled out an online questionnaire. Podcasts are a flexible medium for learning English, according to one study. As a result of this research, it can be concluded that podcasts have become an interesting way to practice English listening skills.